2017
DOI: 10.1002/2016wr020016
|View full text |Cite
|
Sign up to set email alerts
|

Critical zone structure controls concentration‐discharge relationships and solute generation in forested tropical montane watersheds

Abstract: Concentration‐discharge (C‐Q) relationships are poorly known for tropical watersheds, even though the tropics contribute a disproportionate amount of solutes to the global ocean. The Luquillo Mountains in Puerto Rico offer an ideal environment to examine C‐Q relationships across a heterogeneous tropical landscape. We use 10–30 years of weekly stream chemistry data across 10 watersheds to examine C‐Q relationships for weathering products (SiO2(aq), Ca2+, Mg2+, and Na+) and biologically controlled solutes (disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 74 publications
(172 reference statements)
6
84
1
Order By: Relevance
“…In contrast to most studies from forested catchments showing predominantly preevent water contributions to stormflow (Klaus & McDonnell, 2013), the high correlation between large rainfall events and runoff generation with high event water contributions (ranging from 42.4±0.3% up to 98.2±0.3% of the total discharge) indicated that surface and shallow lateral fluxes with more limited subsurface mixing governed DOC transport to the stream (Mei et al, 2014;Shih et al, 2018;Suhett et al, 2007;Wymore et al, 2017) with a relatively quick response time after the rainfall maxima. The latter coupled with moderate to steep slopes Journal of Geophysical Research: Biogeosciences ( Figure 1a) favored rapid DOC leaching from the canopy and understory providing fresh litter material (Figures 1c and 1d) as well as DOC from the rich organic soil surface toward Quebrada Grande.…”
Section: Key Drivers Controlling Tropical Doc Transport and Exportcontrasting
confidence: 82%
“…In contrast to most studies from forested catchments showing predominantly preevent water contributions to stormflow (Klaus & McDonnell, 2013), the high correlation between large rainfall events and runoff generation with high event water contributions (ranging from 42.4±0.3% up to 98.2±0.3% of the total discharge) indicated that surface and shallow lateral fluxes with more limited subsurface mixing governed DOC transport to the stream (Mei et al, 2014;Shih et al, 2018;Suhett et al, 2007;Wymore et al, 2017) with a relatively quick response time after the rainfall maxima. The latter coupled with moderate to steep slopes Journal of Geophysical Research: Biogeosciences ( Figure 1a) favored rapid DOC leaching from the canopy and understory providing fresh litter material (Figures 1c and 1d) as well as DOC from the rich organic soil surface toward Quebrada Grande.…”
Section: Key Drivers Controlling Tropical Doc Transport and Exportcontrasting
confidence: 82%
“…Many studies have observed enrichment behavior for DOC with increases in river discharge (e.g., Herndon et al, ; Hinton et al, ; Hornberger et al, ; Koenig et al, ; Shanley et al, ; Wymore et al, ), and similarly in lakes, wet years have been associated with increased DOC concentrations (Strock et al, ). Despite these well‐documented relationships between DOC and discharge at other sites we did not observe a response of DOC concentration to discharge in this 15‐year record of weekly observations.…”
Section: Discussionmentioning
confidence: 99%
“…Power law equations of the form C = aQ – k enable synoptic comparisons of C‐Q relations across multiple systems where the slope k can be related to potential CZ structural controls. For example, Wymore et al () used 10–30 years of weekly stream chemistry and discharge data across 10 watersheds in Luquillo CZO (Puerto Rico, USA) to show that vegetation, lithology and basin order exert strong controls over the power law exponent for both weathering products (Si, Ca, Mg, Na, and SO 4 ) and biologically controlled solutes (DOC, PO 4 , and inorganic N). In a study of C‐Q relations in headwater streams of the Sierra Nevada, Hunsaker and Johnson () observed chemostatic behavior for bedrock‐derived solutes and nonchemostatic behavior for biologically active solutes, with the former showing slight dilution and the latter, deriving from soil solutions, showing increased concentration during storm events.…”
Section: Special Section On Concentration‐discharge Relations In the mentioning
confidence: 99%